Sensitive polarographic electrochemical determination of clarithromycin in blood serum - Jain, Ashish (2013)
Clarithromycin is an antibacterial widely used for the treatment of a myriad of infections. Various methods including HPLC have been reported for its drug plasma concentration but they are more complex. In this study, we developed an electrochemical method for estimation of clarithromycin in blood using differential pulse polarography (DPP) after oral administration of pure clarithromycin suspension. The differential pulse polarography of clarithromycin showed peak with peak potential Ep is −1460 mV SCE at pH 6.5 ± 0.1. The developed electrochemical method was standardized and validated for the determination of clarithromycin in blood serum of albino rats. PK analysis included C(max), T(max), AUC(0-24), elimination rate constant (K(el)) and t(1/2). C(max) were found to be 1.34 ± 0.16 mg/ml and 1.99 ± 0.22 mg/ml for plain clarithromycin and suspension formulation, respectively. Effects of ammonium tartarate concentration and pH were also studied as specificity parameters. Developed electrochemical method was found to be simple, accurate method for to estimate blood-clarithromycin profile and can also be used similarly for various dosage forms.